Linguistic and Artistic Representations of Trauma : The Contribution of Pedagogies of Discomfort in Language Education - Porto, Melina (The Modern Language Journal.)
This article aims to contribute to recent discussions on pedagogy of pain in world language education. Drawing on the limitations of language to represent and express trauma and pain, we foreground the value of pedagogies at the intersection of language, art, and trauma. It is our contention that a linguistic perspective in and of itself is insufficient and needs to be supported by artistic and multimodal forms of expression as those reinforced by the arts. We describe a study that addressed trauma in a language education context and show how linguistic and nonlinguistic representations of trauma and pain can be productively engaged in formal educational settings using the notion of pedagogy of discomfort. We conclude by highlighting that engaging with the limits of the (un)sayable linked to traumatic and painful events and experiences complementing linguistic with nonlinguistic means can benefit applied linguistics and world language education by bringing attention to the embodied and affective complexities emerging from engagement with trauma.